Системный проект технического университета - Агранович Б. Л. Борис Львович; Похолков Ю. П. Юрий Петрович; Семкин Б. В. Борис Васильевич; Ушаков В. Я. Василий Яковлевич; Чудинов В. Н. Владимир Николаевич; Ямпольский В. З. Владимир Захарович (Томск, Изд-во ТПУ, 1995)
В фонде НТБ ТПУ отсутствует